Handbook of the economics of art and culture - Ginsburgh, Victor; Throsby, C. D. (Amsterdam ; Boston [Mass.] : Elsevier North-Holland, 2006)
Emphasizes the economic aspects of art and culture, a relatively new field that poses inherent problems for economics, with its quantitative concepts and tools. With its focus on culture rather than the arts, this book offers a rigorous description that avoids common problems associated with art and culture scholarship.
Revised papers from a conference held in Sept. 2004 at Princeton University.
Includes bibliographical references and indexes.
oif 27/04/15
Loan
Keywords: Arts -- Economic aspects -- Congresses; Art -- Economic aspects -- Congresses; Culture -- Economic aspects -- Congresses